2012
DOI: 10.1038/srep00452
|View full text |Cite
|
Sign up to set email alerts
|

Strain induced exciton fine-structure splitting and shift in bent ZnO microwires

Abstract: Lattice strain is a useful and economic way to tune the device performance and is commonly present in nanostructures. Here, we investigated for the first time the exciton spectra evolution in bent ZnO microwires along the radial direction via high spatial/energy resolution cathodeluminescence spectroscopy at 5.5 K. Our experiments show that the exciton peak splits into multi fine peaks towards the compressive part while retains one peak in the tensile part and the emission peak displays a continuous blue-shift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
73
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(84 citation statements)
references
References 33 publications
7
73
0
2
Order By: Relevance
“…In the bending region, the strain along the hexagonal axis [0001] varies linearly from compressive inside to tensile outside as ε = x/ρ where −d/2 ≤ x ≤ d/2, ρ is the local curvature radius, and d is the diameter of the nanowire. The maximum bending strains at the outer and inner edges of the curved nanowire are ε = ± d/2ρ [17,20], respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the bending region, the strain along the hexagonal axis [0001] varies linearly from compressive inside to tensile outside as ε = x/ρ where −d/2 ≤ x ≤ d/2, ρ is the local curvature radius, and d is the diameter of the nanowire. The maximum bending strains at the outer and inner edges of the curved nanowire are ε = ± d/2ρ [17,20], respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The elastic strain engineering becomes even more important in semiconducting micro/nano-structures because they possess much higher mechanical toughness and strength compared to their bulk counterparts [13,14]. For example, significant energy redshifts of the near-band-edge (NBE) luminescence in uniaxial strain modulated ZnO [15] and GaAs [16] nanowires, as well as in curved ZnO [17][18][19][20] and CdS [21] micro/nanowires have been observed. It has also been reported that the elastic strain-gradient can effectively modulate the photoexcited carrier and exciton dynamics in MoS 2 atomic membrane [7,22] and ZnO micro/ nanowires [23,24].…”
Section: Introductionmentioning
confidence: 96%
“…As the temperature increases to 300 K, the lasing wavelengths redshift as a result of the Varshni effect (i). 40 The wavelength shift per Kelvin (i.e., the slope) is much larger for the long NWs (~ 0.08 nm/K) compared to the short NWs (~ 0.02 nm/K). Furthermore, the phonon-mediated effects of (ii) and (iii) would be suppressed under low temperatures (e.g., experimental evidence of the narrowing of the Urbach tail width at lower temperatures is presented in the Supplementary Information Figure S10).…”
mentioning
confidence: 97%
“…In particular, the strong electrical polarization of wurtzite semiconductors such as ZnO and GaN, arising from non-central symmetry and crystallographic polarity, has a profound effect on carrier concentration, energy band structure, photon emission energy, and excitonic behavior [1][2][3][4] . Thus, the nature of the terminating surface on wurtzite crystal, which is intimately associated with the growth direction and the bonding state, can play a crucial role in its electrical, optical, and photophysical features.…”
mentioning
confidence: 99%